Low serum potassium levels and diabetes - An unfavorable combination in patients with heart failure and preserved ejection fraction. (15th October 2020) - Badr Eslam, Roza; Öztürk, Begüm; Panzer, Simon; Qin, Hong; Duca, Franz; Binder, Christina; Rettl, Rene; Dachs, Theresa Marie; Alasti, Farideh; Vila, Greisa; Bonderman, Diana
Abstract: Background: Heart failure with preserved ejection fraction (HFpEF) is among the most common forms of heart failure (HF). We aimed to investigate the prognostic significance of serum potassium levels and its interaction with type-2 diabetes mellitus in patients with HFpEF. Methods: Consecutive HFpEF patients were prospectively included in a registry study. The primary endpoint was a composite of cardiac death or HF hospitalization. Results: 363 HFpEF patients were enrolled (median age: 73.0 years; females: 70.3%). Median serum potassium (K+) was 4.3 mmol/L. A total of 128 (35.3%) patients had type-2 diabetes mellitus, of whom 92 were treated with oral anti-diabetic drugs and 35 with insulin. The study population was divided into two groups, according to their serum potassium levels. Significant differences between the groups were detected with regards to combined endpoint [ n = 27 (61.4%) versus n = 87 (27.3%); p < 0.0001]. Lower serum potassium levels were significantly associated with adverse outcome in the Cox proportional hazard analysis [hazard ratio (HR): 1.83; 95% confidence interval (CI) 1.14–2.94; p = 0.0118]. Further independent predictors of adverse outcome were a history of HF hospitalizations (HR: 2.77; 95% CI 1.82–4.21; p < 0.0001), higher NT-pro BNP (HR: 1.93; 95% CI 1.82–4.21; p = 0.0084) as well as type-2 diabetes mellitus (HR: 1.57; 95% CI 1.05–2.34; p = 0.0027). Patients with diabetes and K+ ≤ 3.71 mmol/L faced the worst outcome as compared to the remainder of the group ( p = 0.0001). Conclusion: In HFpEF patients, the combination of diabetes and low serum potassium levels are associated with an adverse outcome. Highlights: We find prognostic markers in HFpEF. Low serum potassium predicts adverse cardiovascular outcomes in this cohort. Diabetes and higher NT-proBNP independently predict adverse cardiovascular outcomes. Worst outcomes are observed in patients with both low serum potassium and diabetes.